Do firms hedge in order to avoid financial distress costs? New empirical evidence using bank data - Lutz Hahnenstein; Gerrit Köchling; Peter N. Posch (Journal of Business Finance & Accounting, 2021)
We present a new approach to test empirically the financial distress costs theory of corporate hedging. We estimate the ex-ante expected financial distress costs, which serve as a starting point to construct further explanatory variables in an equilibrium setting, as a fraction of the value of an asset-or-nothing put option on the firm's assets. Using single-contract data of the derivatives' use of 189 German middle-market companies that stems from a major bank as well as Basel II default probabilities and historical accounting information, we are able to explain a significant share of the observed cross-sectional differences in hedge ratios. Hence, our analysis adds further support for the financial distress costs theory of corporate hedging from the perspective of a financial~intermediary.
Keywords: 650; bankruptcy costs; corporate hedging; financial distress; derivatives